U.S. adults with diagnosed diabetes enrolled in Medicare by age and insurance type - Barbara H. Bardenheier; Steven Bloom; Linda J. Andes; Xilin Zhou; Stefan Gravenstein; Kai McKeever Bullard (Preventive Medicine Reports, 2025)
Objective: To compare clinical and socioeconomic characteristics of U.S. Medicare beneficiaries overall and with diagnosed diabetes by age group (18–64 years and ≥65 years) and insurance type (traditional fee-for-service [FFS] vs Medicare Advantage [MA]) and to compare the prevalence of diabetes among beneficiaries by age group and type of insurance. Methods: In this retrospective, cross-sectional study from the U.S. Medicare Current Beneficiary Survey (MCBS), we combined data from 2017 to 2022 and conducted an unadjusted, pooled analysis of administrative and survey data, weighted to represent U.S. Medicare beneficiaries. We used logistic regression to assess difference by insurance type in care satisfaction. Results: Beneficiaries more likely to enroll in MA than FFS were the same groups at high risk of diabetes, including non-Hispanic Black (18–64: 21.2 % vs 15.9 %; ≥65: 11.4 % vs 6.5 %) and Hispanic (18–64: 14.4 % vs 8.9 %; ≥65: 11.0 % vs 5.4 %) populations, those with less than a high school education (≥65: 16.4 % vs 9.2 %) or annual income <$25,000 (18–64: 69.0 % vs 64.0 %; ≥65: 34.5 % vs 21.6 %), and full dual-eligible beneficiaries (≥65: 10.5 % vs 6.1 %). Beneficiaries with diabetes enrolled in MA did not differ from those enrolled in FFS in diabetes self-management or satisfaction with healthcare. Conclusions: Subgroups of people at highest risk of diabetes were more likely to enroll in MA. Our findings support studies reporting that people with diabetes self-select into MA, and their lack of difference in satisfaction between FFS and MA may support studies that report MA is no less effective than FFS in diabetes care.